Seroprevalence of Toxoplasma gondii in cats (Felis catus, Linnaeus 1758) living in Lima, Peru - Luis Cerro; Alicia Rubio; Rosa Pinedo; Flavya Mendes-de-Almeida; Beatriz Brener; Norma Labarthe (Revista Brasileira de Parasitologia Veterinária)
The aim of this study was to determine the frequency of infection by T. gondii in cats, by examining serum and fecal samples from animals attended at veterinary clinics in the Metropolitan Region of Lima, Peru. We collected and analyzed 154 cat serum samples and 50 fecal samples, regardless of the age, gender or breed. In parallel with the sample collections, the owners answered an epidemiological questionnaire that investigated the following variables: age group, gender, lifestyle (confined, semi-confined or free-living animals), feeding and hunting habits. The serum and fecal samples were analyzed using indirect hemagglutination (IHA) and coproparasitological tests, respectively. IHA showed that the frequency of cat exposure to T. gondii was 11%. Age and gender showed no association with exposure to the parasite. Exposure among the cats was associated with hunting (x2 = 4.98, p = 0.016) and feeding habits (x2 = 13.34, p = 0.001): those fed with raw meat were more exposed than those fed with commercial cat food (x2 = 9.50, p = 0.004) or with homemade food (x2 = 4.1, p = 0.027). The frequency of cats diagnosed in the chronic phase of T. gondii infection was 88% (15/17). No T. gondii oocysts were found in any of the 50 fecal samples examined.